A SURVEY ON THE WORKING OF MICRO FINANCE INSTITUTIONS - SURABHI SHRIVASTAVA (International Journal of Multidisciplinary Research and Studies, 2020)
The international aid and development community is always on the lookout for fresh concepts and methods with which to combat poverty. Beginning in the early 1980s, microfinance received widespread praise as an efficient method that might help reduce poverty. As a result, its use quickly extended throughout the majority of developing nations. It makes an appealing and straightforward promise to development partners and poor households that poverty reduction is possible via the inclusion of the poor in the financial system.